Optimization of Cellulose Extraction Protocol for the Obtention of Fibers with Immunostimulant Properties to Treat Litopenaeus vannamei Vibriosis - Yánez Vaca, Sabrina Abigail (2020)
Litopenaeus vannamei is the most cultivated shrimp that generates approximately USD 3,652 million in exports in 2019. This industry is constantly threatened by different pathogens that cause several diseases. Vibriosis is a high mortality bacterial disease that can cause severe economic losses. Since shrimps have a non-specific immune system, the vaccination does not generate an immunological memory in shrimp and the use of antibiotics can lead to microbial resistance. In recent studies, the F4 cellulose fiber has been identified as a good immunostimulant in white shrimp, showing a mortality reduction by 60% in shrimps infected with Vibrio parahemolyticus. Nonetheless, the extraction protocol used to obtain pure F4 fiber is costly and takes from 4 to 5 hours. In this research, variants of the established protocol (T1, T2, T3…) are evaluated to identify an optimized extraction method. The physical and chemical fiber characterization was performed by SEM, XRD, and FTIR analysis at Yachay Tech and ESPE University. The superoxide anion (O2-) test was carried out in shrimp hemocytes using F4 fibers at different doses (0.5, 1.5, 10 mg/ml). Besides, a toxicity test was done to evaluate the fibers at a dose of 10 mg/ml and their effect on cell viability. In this study, an optimized variant of the established protocol was identified (T9) to extract F4 fibers with immunostimulant properties in white shrimp hemocytes reducing extraction cost by 72.3 % and extraction time from 4 to 2.5 hours.